Presentation essentials: the tools you need to captivate your audience, deliver your story, and make your message memorable - Bruce, Anne 1952-; Love, Sardek (McGraw Hill-Ascent Audio, 2022)
Whether you are in a one-on-one meeting with your supervisor or pitching a new idea to a packed conference room of peers and leaders, knowing how to craft and deliver engaging presentations is an essential skill in every line of business. Confidence is key in every presentation-and sharpening your skills is the most direct route to building it. Presentation Essentials includes: - Lessons including how to build your signature style, structure a powerfully engaging presentation, unleash the power of storytelling, and understand the different type of presentations - "Essential Takeaways" at the end of each chapter ensure you walk away remembering special key points - Part I includes everything you need to know about crafting powerful presentations, memorable catchphrases, one-liners, and visually stunning slides - Part II begins with a presentation skills self-assessment and guides you to apply the essentials in various presentations including speeches, training, information delivery, persuasive talks, and more - Part III includes a skills feedback tool, information on delivering presentations for a living (as a speaker, trainer, coach, or consultant), and more